Criminalized power structures: the overlooked enemies of peace - Dziedzic, Michael J. (Peace and security in the 21st century series, 2016)
Introduction / Michael Dziedzic -- Bosnia : third entity movement / Karmen Fields and Oscar Vera -- Guatemala : the clandestine security apparatus / Carlos Castresana -- Sierra Leone : the Revolutionary United Front / Ismail Rashid -- Haiti : gangs of Cité Soleil / David Beer -- Kosovo : the Kosovo Liberation Army / Michael Dziedzic, Laura Mercean, and Elton Skendaj -- DRC : March 23 Movement / Jana Nyerges -- Afghanistan : Criminal Patronage Networks / Carl Forsberg and Tim Sullivan -- Iraq : Jaish al-Mahdi / Phil Williams and Dan Bisbee -- Colombia : paramilitaries / Jennifer S. Holmes -- Iraq : the rise, fall and persistence of the Maliki regime / Dan Bisbee -- Conclusions / Michael Dziedzic -- An overview of the international toolkit for subduing criminalized power structures / Michael Dziedzic -- Recommendations / Michael Dziedzic